2003
DOI: 10.1007/s11741-003-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on modeling stability of planning inventory and incentive effects

Abstract: Abslract The incentive effects and dynamic aspects of the inventory system were discussed in this paper. The wage policy was regarded as a factor to influence workers' thinking of their action. A multiple objective problem was constructed for the owners and the workers. At the same time, the planning stability is considered in the presented model. Since the process speed is decided by the dynamic demand of production or the interior system itself, two situations were discussed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…[20] In addition, the use of HQD in combination with valsartan significantly delayed the disease progression in patients with DKD stage III or IV; reduced the levels of 24 h urine protein, UACR, glycated hemoglobin, serum cystatin C, and inflammatory factors such as CD4 + T, CD8 + T, TNF-α, and IL-6; and significantly reduced the Chinese medicine symptom scores in patients with DKD stage IV. [21][22][23] HQD plays a role in improving glucolipid metabolism disorders in patients with DKD. A randomized, double-blind, placebo-controlled trial showed that after 12 weeks of treatment with HQD in combination with valsartan, patients with stage III DKD had significantly better TCM efficacy, TCM syndrome score, UACR, fasting and 2-hour postprandial glucose, glycosylated hemoglobin, and lipids than those treated with valsartan alone.…”
Section: Clinical Application Of Hqd For Treating Dkdmentioning
confidence: 99%
“…[20] In addition, the use of HQD in combination with valsartan significantly delayed the disease progression in patients with DKD stage III or IV; reduced the levels of 24 h urine protein, UACR, glycated hemoglobin, serum cystatin C, and inflammatory factors such as CD4 + T, CD8 + T, TNF-α, and IL-6; and significantly reduced the Chinese medicine symptom scores in patients with DKD stage IV. [21][22][23] HQD plays a role in improving glucolipid metabolism disorders in patients with DKD. A randomized, double-blind, placebo-controlled trial showed that after 12 weeks of treatment with HQD in combination with valsartan, patients with stage III DKD had significantly better TCM efficacy, TCM syndrome score, UACR, fasting and 2-hour postprandial glucose, glycosylated hemoglobin, and lipids than those treated with valsartan alone.…”
Section: Clinical Application Of Hqd For Treating Dkdmentioning
confidence: 99%